Association between various types of corticosteroids and mortality for severe community-acquired pneumonia in adults: a systematic review and network meta-analysis - Wang, Peng; Wan, Jun; You, Qiaoyu; Zheng, Yuxin; Xu, Wenhao; He, Jialing; Peng, Liyuan; Jorge Luis, Cuyubamba Dominguez; Feng, Yuning; Xu, Ping; Li, Xinrong; Chong, Weelic; et al. (Frontiers in Pharmacology, 2024)
Objective: This study aims to conduct a systematic review and network meta-analysis to evaluate the efficacy and safety of specific corticosteroids, including but not limited to hydrocortisone, methylprednisolone, prednisolone, and dexamethasone, in the treatment of severe community-acquired pneumonia (SCAP). Efficacy will be assessed using specific outcomes, such as 30-day mortality and the requirement for mechanical ventilation. Safety evaluations will include adverse events like gastrointestinal bleeding and healthcare-associated infections. The study seeks to address the gaps identified in the latest guidelines regarding the optimal use of different corticosteroid types and to provide recommendations for clinical practice. Data sources: This study conducted a comprehensive search of Medline, Embase, and the Cochrane Central Register of Controlled Trials, covering the period from inception until June 22, 2023. Randomized clinical trials for corticosteroid use among adults with SCAP were collected. Study selection: Two researchers independently assessed study eligibility based on titles and abstracts, with any disagreements resolved through discussion or consultation with a third researcher. Data extraction: Two researchers independently collected and clarified study details, with a third researcher adjudicating in case of disputes.The data from 13 randomized clinical trials involving 2495 patients, were analyzed using a random-effects model. Eleven trials were assessed as low risk, while two were assessed as high risk. Trials were rated as having low bias risk. Results, presented as risk ratios (RR) with a 95% confidence interval (CI), indicated that hydrocortisone outperformed prednisolone (RR 0.35; 95% CI 0.10-0.94), methylprednisolone (RR 0.41; 95% CI 0.15-0.89), and placebo (RR 0.35; 95% CI 0.16-0.59) 字体: (默认)Times New Roman, 三号, 加粗, 字距调整: 0 磅 设置格式[Peng Wang]: 左, 孤行控制 设置格式[Peng Wang]: 删除[Peng Wang]: severe community-acquired pneumonia 删除[Peng Wang]: trials 删除[Peng Wang]: in reducing 30-day mortality. A rankogram plot suggested that hydrocortisone had the highest probability of being the most effective treatment for this outcome within the analyzed group.In this network meta-analysis, while hydrocortisone showed greater efficacy than prednisolone, methylprednisolone, and placebo in reducing 30-day mortality in patients with SCAP, further Randomized Controlled Trials (RCTs) are required to confirm these findings before drawing definitive conclusions.